2020
DOI: 10.3390/cancers12113084
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of High-Dose Rabeprazole Plus Metronomic Capecitabine in Advanced Gastro-Intestinal Cancer: A Randomized Phase II Trial

Abstract: Background: In recent years, proton pump inhibitors (PPIs) have been investigated at high-dose to modulate tumor microenvironment acidification thus restoring chemotherapeutic sensitivity. This is the first trial to study activity and safety of repurposing high dose rabeprazole combined with metronomic capecitabine (mCAP). Methods: A phase II study in which patients with gastrointestinal cancer, refractory to standard treatments, who had a life expectancy >3 months, were blind randomized 1:1 to mCAP, 1500 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…However, two “infrequently mentioned” post hoc analyses of RCT, Yang et al (2017) and Roberto et al (2020) , demonstrated PPI use during the capecitabine treatment window was not associated with decreased efficacy in advanced gastric and gastrointestinal cancers, respectively. Such variations in conclusions between Chu et al (2017) and Yang et al (2017) and Roberto et al (2020) may have arisen due to the distinctive feature of the TRIO013 trial ( Hecht et al, 2016 ), which enrolled patients with HER-2 overexpression. Studies have recognized the pivotal role of ethnicity in responses to the treatment in HER-2 amplification ( Killelea et al, 2015 ; Yi et al, 2016 ) and convincing data has also suggested that the response to lapatinib, a tyrosine kinase inhibitor of HER-2, be different across ethnic groups ( Hecht et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two “infrequently mentioned” post hoc analyses of RCT, Yang et al (2017) and Roberto et al (2020) , demonstrated PPI use during the capecitabine treatment window was not associated with decreased efficacy in advanced gastric and gastrointestinal cancers, respectively. Such variations in conclusions between Chu et al (2017) and Yang et al (2017) and Roberto et al (2020) may have arisen due to the distinctive feature of the TRIO013 trial ( Hecht et al, 2016 ), which enrolled patients with HER-2 overexpression. Studies have recognized the pivotal role of ethnicity in responses to the treatment in HER-2 amplification ( Killelea et al, 2015 ; Yi et al, 2016 ) and convincing data has also suggested that the response to lapatinib, a tyrosine kinase inhibitor of HER-2, be different across ethnic groups ( Hecht et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This trial is considered a landmark study that supports the idea of detrimental effects of PPIs on capecitabine. However, two “infrequently mentioned” post hoc analyses of RCT, Yang et al (2017) and Roberto et al (2020) , demonstrated PPI use during the capecitabine treatment window was not associated with decreased efficacy in advanced gastric and gastrointestinal cancers, respectively. Such variations in conclusions between Chu et al (2017) and Yang et al (2017) and Roberto et al (2020) may have arisen due to the distinctive feature of the TRIO013 trial ( Hecht et al, 2016 ), which enrolled patients with HER-2 overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, we have included a total of 17 studies out of the original 96 studies brought up from our searching keywords [4,8,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. These 17 studies were relevant and had su cient data, and were hence included in the review and meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, a systematic review was done by Viñal et al speci cally to assess the effect of PPIs on the e cacy on capecitabine [14], with most of the studies in the original review till 2019 being includedsave for one study that was excluded due to the non-speci cation of the type of acid-suppression therapy used. In addition, when it comes to the studies in the review reported to show signi cant results, one of the studies included as a conference [16], released the full trial paper in 2020 with additional study subjects [17]. This discrepancy in the results of the studies included in this review, the publishing of newer studies after that, as well as the absence of any meta-analysis studies on this particular interaction between both drugs has created a need for a wholesome review assessing not only the risks; but also the bene ts of PPIs on the use of capecitabine, has led to the birth of this systematic review and metaanalysis.…”
Section: Introductionmentioning
confidence: 99%